Joseph Vachal (1838–1911): French entomologist and politician - Rasmussen, Claus (Zootaxa, 2012)
Joseph Vachal (1838–1911) was a French notary and politician who discovered 786 new species and 18 new subspecies of Hymenoptera, 630 of which are still valid and in use today. This makes Vachal a little-known yet the fifth most prolific describer ever of new bee taxa. The present catalog provides a brief biography of Vachal and a complete list of the taxa proposed by Vachal, including a bibliography of his 48 entomological publications. The catalog lists for all valid names published details on the type series, type locality, and collector. A tentative current combination is provided for all taxa based on literature.